2021
DOI: 10.3350/cmh.2021.0155
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir/velpatasvir plus ribavirin for Child-Pugh B and Child-Pugh C hepatitis C virus-related cirrhosis

Abstract: Background/Aims: Real-world studies assessing the effectiveness and safety of sofosbuvir/velpatasvir (SOF/VEL) plus ribavirin (RBV) for Child-Pugh B/C hepatitis C virus (HCV)-related cirrhosis are limited. Methods:We included 107 patients with Child-Pugh B/C HCV-related cirrhosis receiving SOF/VEL plus RBV for 12 weeks in Taiwan. The sustained virologic response rates at off-treatment week 12 (SVR 12 ) for the evaluable population (EP), modified EP, and per-protocol population (PP) were assessed. The safety pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Although there were few patients with decompensated LC in our study, high SVR12 rates in both compensated and decompensated LC support the treatment guidelines of KASL and previous studies [ 20 , 32 ]. As glecaprevir/pibrentasvir is contraindicated for decompensated LC and SOF/velpatasvir, an effective DAA for decompensated LC [ 33 ], is still not approved in South Korea, our promising results of LDV/SOF plus ribavirin in decompensated LC provide the possibility of successful HCV treatment in these Korean patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were few patients with decompensated LC in our study, high SVR12 rates in both compensated and decompensated LC support the treatment guidelines of KASL and previous studies [ 20 , 32 ]. As glecaprevir/pibrentasvir is contraindicated for decompensated LC and SOF/velpatasvir, an effective DAA for decompensated LC [ 33 ], is still not approved in South Korea, our promising results of LDV/SOF plus ribavirin in decompensated LC provide the possibility of successful HCV treatment in these Korean patients.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent multicenter study of 107 patients with Child-Pugh B or C cirrhosis reported SVR 12 rates in evaluable and per-protocol populations of 89.7% and 100%, respectively, with SOF/VEL plus RBV for 12 weeks. 4 In addition, in another study of the most difficult-to-treat population with combined liver and kidney failure who were treated with full-dose SOF/VEL and renally adjusted RBV for 12 weeks, the SVR 12 remained excellent under judicious monitoring. 5 In line with the findings of Su et al, patient tolerability was generally good and the causal relationship between SOF-based DAAs and severe adverse events was limited in our studies.…”
Section: Dear Editormentioning
confidence: 99%
“…5 In line with the findings of Su et al, patient tolerability was generally good and the causal relationship between SOF-based DAAs and severe adverse events was limited in our studies. [2][3][4][5] This is particularly relevant for patients with decompensated HCV-related cirrhosis because a shortage of organs limits accessibility to transplantation. Although a significant proportion of patients with SVR 12 have improved Child-Pugh and model for end-stage liver disease scores, a short-term state of score "purgatory" does not necessarily reflect long-term clinical improvement, and hence prudent surveillance is needed to secure long-term outcomes.…”
Section: Dear Editormentioning
confidence: 99%
“…Most of the patients followed for up to four years after treatment with DAAs had only marginal improvements of the MELD score, showing that liver dysfunction persists [ 8 , 9 ]. It was also reported that about 30% of patients had an improved MELD score ≥ 3 at sustained virologic response rates at off-treatment week 12 when treated with sofosbuvir/velpatasvir plus ribavirin [ 10 ]. Notably, DAA therapy is similarly effective in HCV patients with and without liver cirrhosis [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that about 30% of patients had an improved MELD score ≥ 3 at sustained virologic response rates at off-treatment week 12 when treated with sofosbuvir/velpatasvir plus ribavirin [ 10 ]. Notably, DAA therapy is similarly effective in HCV patients with and without liver cirrhosis [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%